Network Governance in Public Transport Integration Policy: Institutional Coordination and Regulatory Design in Jakarta’s JakLingko Program - Muhammad Ziyad Zainudin; Raihan Raditya; Waki Muhammad Rizki; Az Radzi Atha Setiawan; Fatkhuri Fatkhuri; Ridwan Ridwan (Advances in Public Law and Policy, 2026)
Purpose: This study examines the formulation and implementation of Jakarta’s public transport integration policy, specifically focusing on the JakLingKo program introduced in 2018. It investigates how the program integrates multiple transport modes through unified route management, institutional coordination, and a digital account-based fare system. Methodology/approach: This study uses a qualitative research design based on a systematic literature review and genealogical discourse analysis. An interpretive–constructivist framework is applied to conceptualize policy as the product of historically embedded institutional interactions and power relations. Results: The study finds that JakLingko operates within a network governance arrangement, involving interdependence and collaboration among public and private actors. However, the effectiveness of the program is constrained by fragmented institutional authority, uneven funding structures, and persistent coordination challenges. Conclusions: The research concludes that successful transport integration requires not only coordination mechanisms but also clear institutional mandates and political authority to address the governance challenges in Jakarta’s public transport system. Limitations:. The study’s findings may be limited by the scope of the literature reviewed and the specific context of Jakarta, which might not be fully generalizable to other cities with different governance structures or transport systems. Contributions: The study contributes to urban governance literature by demonstrating that collaborative transport integration, such as JakLingko, requires a holistic approach that combines effective coordination, clear mandates, and strong political authority to overcome governance challenges.